A dynamically cross-linked anisotropic thermally conductive flame-retardant composite material and a preparation method thereof
Through the technologies of the heterosexual heat -derived flame -retardant composite material technology of dynamic cross -linking, the combination of modified boron nitrate@metal oxide hybrid fillers and epoxy resin solves the problem of composite material heat conduction, electrical insulation and flame retardant performance , And realize the recycling and cycle regeneration of the materials, reducing the waste of resource and environmental pollution.
Patent Information
- Application Number
- CN202411347487.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Existing composite materials have shortcomings in thermal conductivity, electrical insulation properties and flame retardant properties, and are difficult to recycle, resulting in waste of resources and environmental pollution.
The composite composite material of the heterosexual heat derived combustion retardant with dynamic cross -linking is used to mix the boron nitride@metal oxide hybrid fillers with epoxy resin through the hybrid of the load. , Activating a dynamic sulfur bond with a dynamic sulfur bond using a layer -by -layer scraper to achieve gradient solidification.
The high thermal conductivity, electrical insulation and excellent flame retardant performance of composite materials have been realized, and the problem of combustion and flame retardant performance is difficult to couple. The material can reshape processing and recycling, reducing the waste of resource and environmental pollution.
Smart Images

Figure CN118879034B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite material preparation, and more specifically, to a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material and its preparation method. Background Technology
[0002] With the increasing integration and miniaturization of electronic devices, the operating frequency and energy density of electronic components are constantly increasing. During prolonged operation, electronic devices generate a significant amount of heat, inevitably affecting the reliability and lifespan of these components. High thermal conductivity electronic packaging materials have become crucial for ensuring the stable operation of electronic devices. Epoxy resin, a lightweight, inexpensive thermosetting material with high mechanical strength, excellent electrical insulation, and good chemical stability, is widely used in electronic packaging. However, ordinary epoxy resins not only have a very low intrinsic thermal conductivity, failing to meet the actual heat dissipation requirements of electronic devices, but also possess extremely high flammability. Furthermore, the increased power consumption and heat accumulation in electronic devices further exacerbate the fire risk. Therefore, designing and preparing epoxy resin packaging materials that combine high thermal conductivity and good flame retardant properties is of significant theoretical and practical importance for ensuring the safe and stable operation of electronic devices.
[0003] Currently, thermally conductive and flame-retardant composite materials are mainly prepared by compounding thermally conductive fillers and flame retardants into a polymer matrix. To achieve uniform dispersion of the thermally conductive fillers and flame retardants in the polymer matrix and enhance the interfacial bonding with the polymer, surface modification is usually performed. However, common organic modifiers such as silane coupling agents often possess a certain degree of flammability and have little effect on improving the flame-retardant properties of the composite material. In recent years, researchers have combined the advantages of catalytic carbonization of organic flame retardants and the nano-barrier effect of two-dimensional fillers, grafting flame retardant molecules onto the surface of two-dimensional thermally conductive filler graphene to prepare various polymer-based composite materials with good flame-retardant effects and thermal conductivity. However, it is worth noting that the excellent electrical conductivity of graphene limits its application in electrical insulation materials. In contrast, hexagonal boron nitride (h-BN) combines good thermal conductivity and electrical insulation properties, showing significant advantages in thermal management of electronic devices. However, h-BN has extremely high chemical inertness, few surface active groups, and a very low grafting rate of flame retardants. Furthermore, directly combining modified boron nitride with epoxy resin makes it difficult to achieve an efficient thermal conductivity pathway, and the improvement in the thermal conductivity and flame retardant effect of the composite material remains limited. On the other hand, the three-dimensional cross-linked network structure of traditional epoxy resins makes it difficult to recycle and reuse the cured composite material, resulting in serious resource waste and environmental pollution. Therefore, it is urgent to explore new methods to achieve thermal conductivity and flame retardancy of epoxy resins, and to introduce dynamic covalent bonds to enable the repeated processing of epoxy composite materials, so as to prepare epoxy encapsulation materials that combine high thermal conductivity, electrical insulation, excellent flame retardant properties, and recyclability. Summary of the Invention
[0004] Based on this, in order to solve the problems of poor thermal conductivity, electrical insulation, and flame retardant properties, and difficulty in recycling of composite materials in the prior art, this invention provides a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material and its preparation method, the specific technical solution of which is as follows:
[0005] A dynamically crosslinked anisotropic thermally conductive and flame-retardant composite material, wherein the anisotropic thermally conductive and flame-retardant composite material forms an oriented structure; the anisotropic thermally conductive and flame-retardant composite material comprises the following raw materials in parts by weight: 5-50 parts of modified boron nitride@metal oxide hybrid filler loaded with hyperbranched flame retardant, 100 parts of epoxy resin, and 15-25 parts of curing agent containing disulfide bonds.
[0006] In addition, the present invention provides a method for preparing a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material, the preparation method comprising the following steps:
[0007] S1. Add boron nitride and metal salt in a mass ratio of 9:1 to 6:4 to an ethanol aqueous solution, sonicate, add ammonia to adjust the pH value, stir the reaction, centrifuge, wash and dry, and then calcine at high temperature to obtain boron nitride@metal oxide hybrid filler.
[0008] S2. Add an equimolar ratio of coupling agent and flame retardant to an organic solvent, add triethylamine and stir to react, and obtain a liquid product after vacuum distillation; then disperse the liquid product and boron nitride@metal oxide hybrid filler in an ethanol aqueous solution, stir at 50℃~80℃ for 1h~5h, centrifuge, wash and dry to obtain modified boron nitride@metal oxide hybrid filler loaded with hyperbranched flame retardant;
[0009] S3. Modified boron nitride@metal oxide hybrid filler loaded with hyperbranched flame retardant is mixed evenly with epoxy resin, and then a curing agent containing disulfide bonds is added. An oriented composite film containing dynamic disulfide bonds is prepared by layer-by-layer film scraping method, and gradient curing is performed to obtain a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material.
[0010] Furthermore, in step S1, the pH value is 9~12, the stirring reaction time is 1h~5h, and the high-temperature calcination temperature is 300℃~500℃.
[0011] Further, the metal salt mentioned in step S1 includes at least one of cerium nitrate, cerium sulfate, cerium acetate, stannous sulfate, tin nitrate, tin acetate, tin tetrachloride, zinc nitrate, zinc sulfide, zinc chloride, titanium sulfate, titanium tetrachloride, cobalt sulfate, cobalt acetate, cobalt nitrate, and cobalt chloride.
[0012] Furthermore, the coupling agent in step S2 is vinylsilane, and the flame retardant is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0013] Further, the vinyl silane includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, (3-acryloyloxypropyl)trimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, and vinyltri(2-methoxyethoxy)silane.
[0014] Furthermore, the organic solvent in step S2 includes at least one of acetone, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, ethyl acetate, and carbon tetrachloride.
[0015] Furthermore, the conditions for centrifugal washing and drying are as follows: centrifugation washing at a speed of 3000 r / min to 10000 r / min, washing 2 to 5 times, and drying at a temperature of 60℃ to 120℃.
[0016] Further, the epoxy resin in step S3 is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, alicyclic epoxy resin, phenolic epoxy resin, and organosilicon modified epoxy resin.
[0017] Further, the curing agent containing disulfide bonds in step S3 is at least one of 4,4'-dithiodiphenylamine, 2,2-(ethylenedithio)diphenylamine, cystamine, 4,4'-dithiodibenzoic acid, and 4,4'-dithiodipropionic acid.
[0018] In the above scheme, modified boron nitride@metal oxide hybrid fillers loaded with hyperbranched flame retardants are prepared and applied to the preparation of composite materials. The construction of the hybrid filler can effectively improve the surface active reaction sites of boron nitride and boron nitride nanosheets, thereby effectively improving the loading rate of the flame retardant on the boron nitride surface. Moreover, thanks to the bridging of the surface metal oxides, the composite material can form a better thermal conductivity pathway. On the other hand, the loading of hyperbranched flame retardants can prevent the migration and efflux of small molecule flame retardants in the composite material, reducing the loss of flame retardants and environmental pollution. In addition, the loading of hyperbranched flame retardants can promote the uniform dispersion of boron nitride hybrid fillers in epoxy resin, enhance the interfacial bonding between the filler and the resin matrix, and thus improve the mechanical properties of the composite material. The metal oxides on the surface of the hybrid filler have a catalytic carbonization effect, which can synergistically improve the flame retardant performance of the composite material with the hyperbranched flame retardant. Furthermore, the anisotropic thermally conductive and flame-retardant composite material prepared by this invention possesses high thermal conductivity, electrical insulation, and excellent flame-retardant properties, overcoming the contradiction of difficulty in coupling and controlling thermal conductivity and flame-retardant properties. In addition, the anisotropic thermally conductive and flame-retardant composite material can be reshaped, processed, and recycled, effectively alleviating the pollution problem of current electronic waste. Compared with other orientation methods in the prior art, such as magnetic field orientation, electric field orientation, ice template method, and 3D printing, the preparation method of this invention is simple, efficient, environmentally friendly, low-cost, and highly practical, showing significant application prospects in the field of electronic packaging. Attached Figure Description
[0019] Figure 1 This is a TEM image of the boron nitride@cerium dioxide hybrid filler prepared in Example 1 of the present invention;
[0020] Figure 2 This is a SEM image of the boron nitride@cerium dioxide hybrid filler prepared in Example 1 of the present invention;
[0021] Figure 3 This is a schematic diagram of the preparation of dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material in Example 1 of the present invention;
[0022] Figure 4 The heat release rate curves are shown for the composite material prepared in Example 1 of this invention and the epoxy composite material containing an equal amount of boron nitride nanosheets.
[0023] Figure 5 The image shows a SEM image of boron nitride and cerium dioxide nanoparticles after direct physical mixing in Comparative Example 2. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to its embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and do not limit the scope of protection of the invention.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0026] An anisotropic thermally conductive and flame-retardant composite material with dynamic crosslinking is provided in this embodiment of the invention. The anisotropic thermally conductive and flame-retardant composite material forms an oriented structure. The anisotropic thermally conductive and flame-retardant composite material comprises the following raw materials in parts by weight: 5-50 parts of modified boron nitride@metal oxide hybrid filler loaded with hyperbranched flame retardant, 100 parts of epoxy resin, and 15-25 parts of curing agent containing disulfide bonds.
[0027] In addition, the present invention provides a method for preparing a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material, the preparation method comprising the following steps:
[0028] S1. Add boron nitride and metal salt in a mass ratio of 9:1 to 6:4 to an ethanol aqueous solution, sonicate, add ammonia to adjust the pH value, stir the reaction, centrifuge, wash and dry, and then calcine at high temperature to obtain boron nitride@metal oxide hybrid filler.
[0029] S2. Add an equimolar ratio of coupling agent and flame retardant to an organic solvent, add triethylamine and stir to react, and obtain a liquid product after vacuum distillation; then disperse the liquid product and boron nitride@metal oxide hybrid filler in an ethanol aqueous solution, stir at 50℃~80℃ for 1h~5h, centrifuge, wash and dry to obtain modified boron nitride@metal oxide hybrid filler loaded with hyperbranched flame retardant;
[0030] S3. Modified boron nitride@metal oxide hybrid filler loaded with hyperbranched flame retardant is mixed evenly with epoxy resin, and then a curing agent containing disulfide bonds is added. An oriented composite film containing dynamic disulfide bonds is prepared by layer-by-layer film scraping method, and gradient curing is performed to obtain a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material.
[0031] In one embodiment, the pH value in step S1 is 9~12, the stirring reaction time is 1h~5h, and the high-temperature calcination temperature is 300℃~500℃.
[0032] In one embodiment, the ultrasonic treatment time in step S1 is 30 min to 60 min.
[0033] In one embodiment, the metal salt in step S1 includes at least one of cerium nitrate, cerium sulfate, cerium acetate, stannous sulfate, tin nitrate, tin acetate, tin tetrachloride, zinc nitrate, zinc sulfide, zinc chloride, titanium sulfate, titanium tetrachloride, cobalt sulfate, cobalt acetate, cobalt nitrate, and cobalt chloride.
[0034] In one embodiment, the mass percentage concentration of the ethanol aqueous solution in step S1 is 80% to 98%.
[0035] In one embodiment, the coupling agent in step S2 is vinylsilane, and the flame retardant is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0036] In one embodiment, the vinyl silane includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, (3-acryloyloxypropyl)trimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, and vinyltri(2-methoxyethoxy)silane.
[0037] In one embodiment, the amount of triethylamine added is 0.5% to 3% of the volume of the organic solvent.
[0038] In one embodiment, the organic solvent in step S2 includes at least one of acetone, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, ethyl acetate, and carbon tetrachloride.
[0039] In one embodiment, the mass percentage concentration of the ethanol aqueous solution in step S2 is 80% to 98%.
[0040] In one embodiment, the conditions for centrifugal washing and drying are as follows: centrifugal washing at a speed of 3000 r / min to 10000 r / min, washing 2 to 5 times, and drying at a temperature of 60°C to 120°C.
[0041] In one embodiment, the epoxy resin in step S3 is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, alicyclic epoxy resin, phenolic epoxy resin, and organosilicon modified epoxy resin.
[0042] In one embodiment, the curing agent containing disulfide bonds in step S3 is at least one of 4,4'-dithiodiphenylamine, 2,2-(ethylenedithio)diphenylamine, cystamine, 4,4'-dithiodibenzoic acid, and 4,4'-dithiodipropionic acid.
[0043] In one embodiment, the layer-by-layer coating method involves coating layers with a thickness of 1 μm to 5 μm each time.
[0044] In one embodiment, the gradient curing temperature is 80℃~150℃ and the time is 1h~3h.
[0045] In one embodiment, the gradient curing is performed by curing at 80°C to 120°C for 1 to 2 hours, then at 120°C to 145°C for 1 to 3 hours, and finally at 150°C for 1 to 3 hours.
[0046] The above scheme, through optimization of composition and process, produces anisotropic thermally conductive and flame-retardant composite materials that combine high thermal conductivity, electrical insulation and excellent flame-retardant properties, overcoming the contradiction that thermal conductivity and flame-retardant properties are difficult to couple and control. Moreover, the anisotropic thermally conductive and flame-retardant composite materials can be reshaped, processed and recycled, which can effectively alleviate the pollution problem of current electronic waste.
[0047] The implementation schemes of the present invention will now be described in detail with reference to specific embodiments.
[0048] Example 1:
[0049] A method for preparing a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material includes the following steps:
[0050] Boron nitride nanosheets and cerium nitrate at a mass ratio of 9:1 were added to an 80% (w / w) aqueous ethanol solution. The mixture was ultrasonically treated for 30 min, and ammonia was added to adjust the pH to 9. The mixture was stirred for 5 h, centrifuged and washed three times at 10000 r / min, dried in a vacuum oven at 60℃, and then calcined at 500℃ for 1 h to obtain the boron nitride@cerium dioxide nano-hybrid filler, as shown in the attached figure. Figure 1 and 2 As shown, cerium dioxide nanoparticles are uniformly bonded to the surface of boron nitride nanosheets, effectively increasing the specific surface area and active reaction sites of the hybrid filler.
[0051] Equimolar amounts of (3-acryloyloxypropyl)trimethoxysilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added to acetone, and 0.5% (by volume) of triethylamine was added and the mixture was stirred and reacted. The liquid product obtained after vacuum distillation was then dispersed with boron nitride@cerium dioxide nano-hybrid filler in a 98% (w / w) aqueous ethanol solution. The mixture was stirred at 50 °C for 5 h, centrifuged and washed three times at 3000 r / min, and dried at 120 °C for 2 h to obtain boron nitride@cerium dioxide hybrid filler loaded with hyperbranched flame retardant.
[0052] By weight, 50 parts of modified boron nitride@cerium dioxide hybrid filler loaded with hyperbranched flame retardant were mixed evenly with 100 parts of bisphenol A epoxy resin, and then 15 parts of 4,4'-dithiodiphenylamine were added. An oriented composite film was prepared by layering the film in 1 μm thicknesses. The film was cured at 80℃ for 2 h, then at 120℃ for 2 h, and finally at 150℃ for 2 h to obtain a dynamically cross-linked anisotropic thermally conductive flame-retardant composite material (preparation flowchart attached). Figure 3 (As shown).
[0053] The thermal conductivity and flame retardant properties of the samples prepared in this embodiment were measured using a thermal conductivity meter and microcalorimetry (specific testing methods are performed according to conventional practices in the field and will not be described in detail in this embodiment). The thermal conductivity of the anisotropic thermally conductive and flame-retardant composite material prepared in this embodiment reached 6.89 W / mK, the flame retardant test achieved V0 level, the limiting oxygen index was 34.5, and the microcalorimetry data showed that the total heat release of the composite material was only 20.1 kJ / g (heat release curve is attached). Figure 4 As shown, the heat release is significantly lower than that of epoxy resin composites containing an equal amount of boron nitride nanosheet filler; in addition, the tensile strength reaches 82.5 MPa. The anisotropic thermally conductive and flame-retardant composite material was pulverized after film formation and hot-pressed at 160℃ and 5 MPa for 15 min to regenerate the anisotropic thermally conductive and flame-retardant composite material. The pulverized anisotropic thermally conductive and flame-retardant composite material was then dispersed in an aqueous acetic acid solution and heated for degradation for 3 h. The degradation solution was dried to obtain chemically degraded and recovered epoxy resin.
[0054] Example 2:
[0055] A method for preparing a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material includes the following steps:
[0056] Boron nitride nanosheets and tin acetate in a mass ratio of 6:4 were added to an ethanol aqueous solution with a mass percentage concentration of 98%. The mixture was ultrasonically treated for 40 min, and ammonia was added to adjust the pH value to 12. The mixture was stirred and reacted for 1 h. After centrifugation and washing 5 times at 3000 r / min, the mixture was dried in a vacuum drying oven at 120℃ and then calcined at 300℃ for 3 h to obtain boron nitride@tin dioxide nano-hybrid filler.
[0057] Equimolar amounts of 3-(methacryloyloxy)propyltrimethoxysilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added to N,N-dimethylacetamide. Triethylamine, accounting for 1% of the volume of N,N-dimethylacetamide, was added and the mixture was stirred and reacted. The liquid product obtained after vacuum distillation was then dispersed with boron nitride@tin dioxide nano-hybrid filler in a 95% (w / w) aqueous ethanol solution. The mixture was stirred at 80 °C for 1 h, centrifuged and washed three times at 5000 r / min, and dried at 100 °C for 4 h to obtain boron nitride@tin dioxide hybrid filler loaded with hyperbranched flame retardant.
[0058] By weight, 30 parts of modified boron nitride@tin dioxide hybrid filler loaded with hyperbranched flame retardant were mixed evenly with 100 parts of bisphenol F epoxy resin, and 20 parts of 2,2-(ethylenedithio)diphenylamine were added. An oriented composite film was prepared by scraping the film layer by layer at a thickness of 2 μm each time. The film was cured at 80℃ for 2 h, then at 120℃ for 2 h, and then at 150℃ for 2 h to obtain a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material.
[0059] The anisotropic thermally conductive and flame-retardant composite material prepared in this embodiment has a thermal conductivity of up to 4.73 W / mK, a flame retardancy rating of V0, a limiting oxygen index of 30.5, and a tensile strength of 84.2 MPa.
[0060] Example 3:
[0061] A method for preparing a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material includes the following steps:
[0062] Boron nitride nanosheets with a mass ratio of 3:1 and zinc nitrate were added to an ethanol aqueous solution with a mass percentage concentration of 90%. The mixture was ultrasonically treated for 60 min, and ammonia was added to adjust the pH value to 10. The mixture was stirred and reacted for 3 h. After centrifugation and washing twice at 5000 r / min, the mixture was dried in a vacuum drying oven at 100℃ and then calcined at 400℃ for 2 h to obtain boron nitride@zinc oxide nano-hybrid filler.
[0063] Equimolar amounts of vinyltris(2-methoxyethoxy)silane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added to ethyl acetate, and 2% (by volume) of triethylamine was added and the mixture was stirred and reacted. The liquid product obtained after vacuum distillation was then dispersed with boron nitride@zinc oxide nano-hybrid filler in a 90% (w / w) aqueous ethanol solution. The mixture was stirred at 60 °C for 3 h, centrifuged and washed three times at 6000 r / min, and dried at 100 °C for 3 h to obtain boron nitride@zinc oxide hybrid filler loaded with hyperbranched flame retardant.
[0064] By weight, 5 parts of modified boron nitride@zinc oxide hybrid filler loaded with hyperbranched flame retardant were mixed evenly with 100 parts of phenolic epoxy resin, and then 25 parts of cystamine were added. An oriented composite film was prepared by scraping the film layer by layer at a thickness of 5 μm each time. The film was cured at 25℃ for 2 h, then at 120℃ for 2 h, and then at 150℃ for 2 h to obtain a dynamically cross-linked anisotropic thermally conductive flame retardant composite material.
[0065] The anisotropic thermally conductive and flame-retardant composite material prepared in this embodiment was found to have a thermal conductivity of 1.13 W / mK, a limiting oxygen index of 28.7, and a tensile strength of 82.4 MPa.
[0066] Example 4:
[0067] A method for preparing a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material includes the following steps:
[0068] Boron nitride and titanium sulfate in a mass ratio of 6:1 were added to an ethanol aqueous solution with a mass percentage concentration of 95%. The mixture was ultrasonically treated for 60 min, and ammonia was added to adjust the pH value to 10. The mixture was stirred and reacted for 4 h. After centrifugation and washing 4 times at 5000 r / min, the mixture was dried in a vacuum drying oven at 100 °C and then calcined at 350 °C for 3 h to obtain the boron nitride@titanium dioxide hybrid filler.
[0069] Equimolar amounts of vinyltrimethoxysilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added to N,N-dimethylformamide. Triethylamine, accounting for 3% of the volume of the N,N-dimethylformamide, was added and the mixture was stirred and reacted. The liquid product obtained after vacuum distillation was then dispersed with boron nitride@titanium dioxide hybrid filler in an 80% (w / w) aqueous ethanol solution. The mixture was stirred at 60°C for 4 h, centrifuged and washed twice at 8000 r / min, and dried at 80°C for 5 h to obtain boron nitride@titanium dioxide hybrid filler loaded with hyperbranched flame retardant.
[0070] By weight, 20 parts of modified boron nitride@titanium dioxide hybrid filler loaded with hyperbranched flame retardant were mixed evenly with 100 parts of alicyclic epoxy resin, and then 20 parts of 4,4'-dithiodibenzoic acid were added. An oriented composite film was prepared by scraping the film layer by layer at a thickness of 2 μm each time. The film was cured at 60 °C for 2 h, then at 100 °C for 2 h, and then at 160 °C for 2 h to obtain a dynamically cross-linked anisotropic thermally conductive flame retardant composite material.
[0071] The anisotropic thermally conductive and flame-retardant composite material prepared in this embodiment was found to have a thermal conductivity of 2.89 W / mK, a limiting oxygen index of 29.3, and a tensile strength of 83.7 MPa.
[0072] Example 5:
[0073] A method for preparing a dynamically cross-linked anisotropic thermally conductive and flame-retardant composite material includes the following steps:
[0074] Boron nitride and cobalt nitrate in a mass ratio of 5:1 were added to an ethanol aqueous solution with a mass percentage concentration of 90%. The mixture was ultrasonically treated for 30 min, and ammonia was added to adjust the pH value to 11. The mixture was stirred and reacted for 2.5 h. After centrifugation and washing three times at 8000 r / min, the mixture was dried in a vacuum drying oven at 100℃ and then calcined at 380℃ for 2 h to obtain the boron nitride@cobalt oxide hybrid filler.
[0075] Equimolar amounts of vinyltriethoxysilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added to chloroform, and 1.5% (by volume) of triethylamine was added and the mixture was stirred and reacted. The liquid product obtained after vacuum distillation was then dispersed with boron nitride@cobalt oxide hybrid filler in a 90% (w / w) aqueous ethanol solution. The mixture was stirred at 70 °C for 2 h, centrifuged and washed 5 times at 3000 r / min, and dried at 60 °C for 5 h to obtain boron nitride@cobalt oxide hybrid filler loaded with hyperbranched flame retardant.
[0076] By weight, 30 parts of modified boron nitride@cobalt oxide hybrid filler loaded with hyperbranched flame retardant were mixed evenly with 100 parts of organosilicon modified epoxy resin, and then 15 parts of 4,4'-dithiodipropionic acid were added. An oriented composite film was prepared by scraping the film layer by layer at a thickness of 3 μm each time. The film was cured at 80℃ for 2 h, then at 100℃ for 2 h, and then at 150℃ for 2 h to obtain a dynamically cross-linked anisotropic thermally conductive flame retardant composite material.
[0077] Tests showed that the anisotropic thermally conductive and flame-retardant composite material prepared in this embodiment has a thermal conductivity of up to 4.45 W / mK, a flame retardancy rating of V0, a limiting oxygen index of 30.8, and a tensile strength of 81.9 MPa.
[0078] Comparative Example 1:
[0079] Compared with Example 1, Comparative Example 1 differs in that the filler used in Comparative Example 1 is boron nitride nanosheets, while the rest is the same as in Example 1.
[0080] Thermogravimetric analysis (TGA) was used to determine the content of hyperbranched flame retardant loaded on the surfaces of boron nitride nanosheets and boron nitride@cerium dioxide hybrid fillers, respectively. The results showed that the loading rate of flame retardant on the surface of boron nitride nanosheets was only 3.1%, while the loading of flame retardant on the surface of the boron nitride@cerium dioxide hybrid filler was as high as 9.4%. This indicates that the construction of the hybrid filler significantly improved the surface activity of the boron nitride nanosheets and effectively increased the loading of flame retardant on the surface of the hybrid filler. Further testing of the sample prepared in this comparative example revealed that the thermal conductivity of the composite material prepared in this comparative example was only 4.20 W / mK, and the limiting oxygen index was 30.8. This indicates that the hybridization of boron nitride nanosheets and metal oxides facilitates the formation of good thermal conductivity pathways, and the surface metal oxides have a good catalytic carbonization effect, which can improve the flame retardant performance of the material.
[0081] Comparative Example 2:
[0082] Compared with Example 1, Comparative Example 2 differs in that the filler used in Comparative Example 2 is a direct physical mixture of boron nitride nanosheets and cerium dioxide nanoparticles; otherwise, it is the same as Example 1.
[0083] From the appendix Figure 5 The SEM images show that after direct physical mixing, the cerium dioxide nanoparticles exhibit severe agglomeration and are not uniformly bonded with the boron nitride nanosheets.
[0084] Further testing of the samples prepared in this comparative example revealed that the thermal conductivity of the composite material prepared in this comparative example was only 3.45 W / mK, which was lower than that of the composite material with direct addition of single boron nitride nanosheets. This is because the intrinsic thermal conductivity of cerium dioxide nanoparticles is lower than that of boron nitride nanosheets. In the case of severe aggregation of cerium dioxide nanoparticles, they cannot play a role in promoting the formation of thermal conduction pathways, so the thermal conductivity is lower than that of Example 1 and Comparative Example 1. In addition, the limiting oxygen index was 31.5, which was lower than that of Example 1. This indicates that the severely aggregated cerium dioxide nanoparticles are difficult to form a good synergistic effect with the nano-barrier effect of boron nitride nanosheets and hyperbranched flame retardants, and their catalytic carbonization effect is not fully utilized.
[0085] Comparative Example 3:
[0086] Compared with Example 1, Comparative Example 3 differs in that 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is added directly, and no hyperbranched flame retardant is prepared by reacting with vinylsilane. Otherwise, it is the same as Example 1.
[0087] Testing of the samples prepared in this comparative example revealed that the thermal conductivity of the composite material prepared in this comparative example was only 5.41 W / mK, the limiting oxygen index was 31.2, and the tensile strength was only 71.3 MPa. This indicates that the synthesis of the hyperbranched flame retardant and its loading modification on the surface of the hybrid filler significantly improved the interfacial bonding between the hybrid filler and the epoxy resin matrix, reduced the interfacial thermal resistance of the composite material, and reduced pores and defects. As a result, the composite material in Example 1 had better thermal conductivity, limiting oxygen index, and tensile strength than the comparative example.
[0088] Comparative Example 4:
[0089] Compared with Example 1, Comparative Example 4 differs in that: after uniformly mixing the boron nitride@cerium dioxide hybrid filler loaded with hyperbranched flame retardant with bisphenol A epoxy resin and curing agent 4,4'-dithiodiphenylamine, it is directly poured into a polytetrafluoroethylene mold for curing. The layer-by-layer film-coating method is not used to prepare the oriented composite film. Otherwise, it is the same as Example 1.
[0090] Testing of the samples prepared in this comparative example revealed that the thermal conductivity of the composite material prepared in this comparative example was only 0.97 W / mK and the limiting oxygen index was 29.8. This indicates that the filler cannot form an oriented structure in the directly cured composite material, which affects the formation of the thermal conductivity path and cannot form a good flame retardant barrier, thus reducing its flame retardant performance.
[0091] Comparative Example 5:
[0092] Compared with Example 1, Comparative Example 5 differs in that the curing agent used in Comparative Example 5 is 4,4'-methylenediphenylamine, while the rest is the same as in Example 1.
[0093] Testing of the samples prepared in this comparative example revealed that the thermal conductivity of the composite material prepared in this comparative example was 6.77 W / mK and the limiting oxygen index was 33.9, which was close to the performance of Example 1. However, the cured composite film could not be repeatedly processed after being crushed, and it did not achieve chemical degradation after being heated in an aqueous acetic acid solution.
[0094] In summary, based on the embodiments and comparative examples, it can be seen that the present invention utilizes boron nitride@metal oxide hybrid filler to load hyperbranched flame retardants, which not only avoids the migration and efflux of small molecule flame retardants in composite materials, reducing flame retardant loss and environmental pollution, but also promotes the uniform dispersion of boron nitride hybrid filler in epoxy resin, enhances the interfacial bonding with the resin matrix, thereby improving the mechanical and thermal conductivity of the composite material. Furthermore, the uniformly distributed metal oxides on the surface of the hybrid filler improve the surface activity of boron nitride and the loading rate of the flame retardant, and have a catalytic carbonization effect, enabling… The invention achieves a good synergistic effect with the barrier effect of hyperbranched flame retardants and boron nitride, resulting in a significant improvement in the flame retardant performance of the composite material. The anisotropic thermally conductive flame-retardant composite material prepared by this invention combines high thermal conductivity, electrical insulation, and excellent flame retardant properties, overcoming the contradiction that thermal conductivity and flame retardant properties are difficult to couple and control. More importantly, the composite material can be reshaped, processed, and recycled, which can effectively alleviate the pollution problem of current electronic waste. Compared with the commonly used orientation methods, the preparation method of this invention is simple, efficient, environmentally friendly, low-cost, and highly practical, and has important application prospects in the field of electronic packaging.
[0095] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0096] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A dynamically cross-linked anisotropic thermally conductive flame-retardant composite material, characterized in that: The anisotropic thermally conductive flame-retardant composite material forms an oriented structure; the anisotropic thermally conductive flame-retardant composite material comprises the following raw materials in parts by weight: 5 to 50 parts of modified boron nitride@metal oxide hybrid filler loaded with hyperbranched flame retardant, 100 parts of epoxy resin and 15 to 25 parts of curing agent containing disulfide bonds; The method for preparing the dynamically cross-linked anisotropic thermally conductive flame-retardant composite material comprises the following steps: S1, adding boron nitride and metal salt in a mass ratio of 9:1 to 6:4 to an ethanol aqueous solution, adding ammonia water to adjust the pH value after ultrasonic treatment, stirring the reaction, washing by centrifugation and drying, and then calcining at high temperature to obtain a boron nitride@metal oxide hybrid filler; S2, adding a coupling agent and a flame retardant in an equal molar ratio to an organic solvent, adding triethylamine for stirring reaction, and obtaining a liquid product after reduced pressure distillation; then dispersing the liquid product and a boron nitride@metal oxide hybrid filler in an ethanol aqueous solution, stirring for 1h~5h at a temperature of 50°C~80°C, centrifugally washing and drying, to obtain a modified boron nitride@metal oxide hybrid filler loaded with a hyperbranched flame retardant; S3, uniformly mixing the modified boron nitride@metal oxide hybrid filler loaded with a hyperbranched flame retardant with an epoxy resin, then adding a curing agent containing a disulfide bond, and preparing an oriented composite film containing a dynamic disulfide bond by a layer-by-layer scraping method, and gradient curing to obtain a dynamically cross-linked anisotropic thermal conductive flame retardant composite material; Wherein: the metal salt in step S1 includes at least one of cerium nitrate, cerium sulfate, cerium acetate, stannous sulfate, tin nitrate, tin acetate, tin tetrachloride, zinc nitrate, zinc sulfide, zinc chloride, titanium sulfate, titanium tetrachloride, cobalt sulfate, cobalt acetate, cobalt nitrate, and cobalt chloride; The coupling agent in step S2 is vinyl silane, and the flame retardant is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
2. The anisotropic thermally conductive flame-retardant composite material according to claim 1, characterized in that: The pH value in step S1 is 9-12, the stirring reaction time is 1h-5h, and the high-temperature calcination temperature is 300°C-500°C.
3. The anisotropic thermally conductive flame-retardant composite material according to claim 1, characterized in that: The vinyl silane includes at least one of vinyl trimethoxy silane, vinyl triethoxy silane, (3-acryloxypropyl) trimethoxy silane, 3-(methacryloxy) propyl trimethoxy silane, and vinyl tris (2-methoxyethoxy) silane.
4. The anisotropic thermally conductive flame-retardant composite material according to claim 1, characterized in that: The organic solvent in step S2 includes at least one of acetone, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, ethyl acetate, and carbon tetrachloride.
5. The anisotropic thermally conductive flame-retardant composite material according to claim 1, characterized in that: The conditions for centrifugal washing and drying are: centrifugal washing at a speed of 3000r / min~10000r / min, the number of washing times is 2~5 times, and the drying temperature is 60℃~120℃.
6. The anisotropic thermally conductive flame-retardant composite material according to claim 1, characterized in that: The epoxy resin in step S3 is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, alicyclic epoxy resin, novolac epoxy resin, and silicone-modified epoxy resin.
7. The anisotropic thermally conductive flame-retardant composite material according to claim 1, characterized in that: In step S3, the curing agent containing a disulfide bond is at least one of 4,4'-dithiodiphenylamine, 2,2-(ethylenedithio)diphenylamine, cystamine, 4,4'-dithiodibenzoic acid, and 4,4'-dithiodipropionic acid.
Citation Information
Patent Citations
Functionalized boron nitride as well as preparation method and application thereof
CN115028893A
Low-thermal-resistance boron nitride heat-conducting gasket and preparation method thereof
CN116120610A